Between Love And Duty Reflected In Lasse Hallstrom's Dear John Movie (2010): A Psychoanalytic Criticism - Hartanti, Ratih Siyam Sri; , Drs. M. Thoyibi, M.S; , Titis Setyabudi S.S., M.Hum (2013)
The major issue of this study is how the tension between love and duty is reflected in Lasse Hallstrom's Dear John movie (2010). The objective of this study is to analyze Lasse Hallstrom's Dear John movie based on the structural elements of the movie and to describe John's feeling when confronted between love and duty in Dear John movie. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The primary data source of the study is Dea John movie directed by Lasse Hallstrom. The secondary data sources are books such as Theories of personality, Theory of Literature, and other sources. The technique of the data analysis is descriptive analysis. The results of the study show as follows. Firstly, Based on the structural analysis, the movie shows that the director wants to deliver a moral message that -people are sometimes confused whether to accomplish their duty or to meet their need for love‖ in order to deliver the message the director wants the character of John who was torn between to love and duty, he than develops the plot and other narrative elements that comprise the structural elements of the movie, so that they are related to one another forming a unity. Secondly based on the psychoanalysis, the director illustrates a psychological phenomenon in which the major character is confronted between his love and his duty as army. It is apparent that the director wants to say that an army should sacrifice to be responsibility for the duty